A MORFOLOGIA NO BRASIL: INDICADORES E QUESTÕES - Basilio, Mararida Maria de Paula (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2018)
This work attempts to give an idea of current development of morphological studies in Brazil. After a brief introduction to the development of Linguistics and morphological studies in Brazil in the period characterized by the creation of ABRALIN, it presents an analyis of the contemporary scene and its relevant tendencies and, as an illustration of contemporary concerns on Morphology in Brazil it summarizes a discussion on research topics taken by the work group of Morphology in the Projeto Gramática do Português Falado.